(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article examines the stages of organizing the internal audit service and its development, the regulatory framework for organizing the internal audit service and its place in corporate governance, foreign experience in internal audit activities and the methodological basis for its application. Based on the objectives of the study, theoretical results and conclusions are presented.